(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The process of teaching and learning foreign languages has been transformed by the integration of modern technologies, innovative methods, and diverse instructional techniques. This article examines how contemporary digital hance learner engagement and language proficiency. It also explores effective pedagogical approaches including communicative language teaching, task-based learning, and blended learning models, which prioritize interaction and real-world usage. Additionally, practical techniques such as scaffolding, the use of authentic materials, and differentiated instruction are discussed as essential elements for addressing varied learner needs. By combining these components, educators can create dynamic, learner-centered environments that support effective and meaningful foreign language acquisition in the 21st century.